2015
DOI: 10.1007/s13277-015-3879-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Rad9A enhanced DNA damage induced by trichostatin A in esophageal cancer cells

Abstract: Histone deacetylase (HDAC) inhibitors have recently emerged as a new class of anticancer agents. As a classical HDAC inhibitor, trichostatin A (TSA) has been shown to possess many anticancer activities such as induction of cell cycle arrest, promotion of cell death, and enhancement of radiosensitity. In our previous work, we found that TSA treatment induced Rad9 gene expression, which suggested that Rad9 might play a role in TSA-induced biological effects. As Rad9 is involved in maintaining genomic integrity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Treatment of cancer cells with broad-spectrum HDAC inhibitors such as vorinostat (suberoylanilide hydroxamic acid, SAHA) and trichostatin A (TSA) enhance DNA damage and impair non-homologous end joining (NHEJ) of DNA double-strand breaks (DSBs) (Lee et al 2010; Pang et al 2016; Robert et al 2016; Vashishta and Hetman 2014). The exact role of single HDAC subtypes including HDAC8 and HDAC10 in DNA damage repair, however, is not yet fully understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of cancer cells with broad-spectrum HDAC inhibitors such as vorinostat (suberoylanilide hydroxamic acid, SAHA) and trichostatin A (TSA) enhance DNA damage and impair non-homologous end joining (NHEJ) of DNA double-strand breaks (DSBs) (Lee et al 2010; Pang et al 2016; Robert et al 2016; Vashishta and Hetman 2014). The exact role of single HDAC subtypes including HDAC8 and HDAC10 in DNA damage repair, however, is not yet fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of DNA damage and inhibition of cellular DNA repair bear the potential to take advantage of malignant cells’ dysfunctional DNA damage response mechanisms and thus drive them into cell death while sparing non-malignant cells (Hosoya and Miyagawa 2014 ; Lord and Ashworth 2012 ). Treatment of cancer cells with broad-spectrum HDAC inhibitors such as vorinostat (suberoylanilide hydroxamic acid, SAHA) and trichostatin A (TSA) enhance DNA damage and impair non-homologous end joining (NHEJ) of DNA double-strand breaks (DSBs) (Lee et al 2010 ; Pang et al 2016 ; Robert et al 2016 ; Vashishta and Hetman 2014 ). The exact role of single HDAC subtypes including HDAC8 and HDAC10 in DNA damage repair, however, is not yet fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Duffy et al ( 2017 ) showed that human cells overexpressing the TDP1 gene were more sensitive to TSA whereas Meisenberg et al ( 2017 ) suggested that TSA influences the repair of DSBs resulting from topo I/DNA cleavage complexes through a TDP1/TDP2-independent mechanism. The study by Pang et al ( 2016 ) showed that TSA induces DSBs in human cancer cells, triggering at the same time the RAD9 ( RADIATION SENSITIVE ) gene expression through promoter hyperacetylation. RAD9 is part of the 9-1-1 complex, early sensor of genotoxic stress, able to control G 1 /S transition.…”
Section: Discussionmentioning
confidence: 99%
“…As a component of RAD9A-HUS1-RAD1 (9-1-1) complex, RAD9A promotes genomic repair when DNA is damaged 33 . As such, abnormal expression of RAD9A has been linked to tumorigenesis 34 . In comparison, MYOG is an important myogenic regulatory factor necessary for myocyte differentiation and the development of functional skeletal muscle 35 .…”
Section: Discussionmentioning
confidence: 99%